If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-3)=4x+8
We move all terms to the left:
3(x-3)-(4x+8)=0
We multiply parentheses
3x-(4x+8)-9=0
We get rid of parentheses
3x-4x-8-9=0
We add all the numbers together, and all the variables
-1x-17=0
We move all terms containing x to the left, all other terms to the right
-x=17
x=17/-1
x=-17
| x/95=162/20 | | 5(-x+2)=13-4(3x-1)= | | 2x-4(x-4)=3x+10-5x+6 | | 9x+5=11+7(x-3) | | 9y=4+5 | | 3m-11=16 | | u2-2/3u+5=0 | | 6x+3=-2x+19 | | 4-2(v-60)=-8 | | 4-2(v-60=-8 | | 2(4h+)=9h-2 | | -8(7+9x)=16 | | -17=3p-5 | | 3(n=5)+2=26 | | 22-6x=24 | | 45/12=30/n | | 4(2x+1)=3x+11 | | -3.7w=155.4 | | (x^2+12)/(x^2-9)=0 | | 63.1=6.1=(0.38)x15 | | 14/21=35/n | | 6x+2-3x=x+7+2x | | x^2+12/x^2-9=0 | | 6x+2-3x=x+72x | | -6x-6(2x-16)=6 | | 2/3=35/n | | 1-(3/8)x=0 | | 8x-5=5-8x | | 45x=211 | | 63.1=6.1-(.08)x(15) | | 4+12x=9x+16 | | 46+4/5+x=360 |